Analysis of Bioactive Components of Oyster Protein Peptide and its Application in Health Food - Guo, Xinyue (Transactions on Environment, Energy and Earth Sciences, 2024)
Oyster protein peptides (OPPs) have attracted a great deal of interest due to their potential health benefits and therapeutic effects. Recent studies have highlighted the rich material composition of OPPs. However, there are still gaps in the understanding of the comprehensive physiological functions and bioavailability of these bioactive substances. In this research, the bioactive components and physiological functions of OPPs were analyzed. The essential amino acids in OPPs support muscle health, energy production, and blood sugar regulation, while glutathione and taurine provide potent antioxidant effects and manage oxidative stress. Zinc enhances immune function and skin integrity and polysaccharides enhance immune cell activity, and vitamins B1, A, and D are essential for DNA synthesis, brain function, and bone health. These findings highlight the potential of OPPs as a valuable ingredient for developing healthy foods. The significance of this research is to promote the development of functional food and nutrition and health care, and promote the sustainable development of oyster farming and processing industry. Future research should focus on clinical trials to determine the therapeutic potential and safety of OPPs, explore the molecular mechanisms behind its bioactive effects, and develop standardized extraction methods to ensure consistency and potency. This research provides a reference for future research and highlights areas that require further investigation, such as the bioavailability of OPPs and the long-term effects on human health.